Water-based composite ceramic dispersant containing high-molecular polymer and preparation method of water-based composite ceramic dispersant
By using a polymer dispersant containing carboxylate and sulfonate in the ceramic dispersant and combining with a small molecule dispersant to form an electrostatic repulsion and hydration membrane stance hindering layer, the solution of ceramic dispersant in the prior art is solved. The narrow rubber range and side effects have achieved efficient dispersion and stability of ceramic raw materials.
Patent Information
- Application Number
- CN202411294395.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing ceramic dispersant has a narrow range of degreasing, has side effects and poor versatility, and cannot be applied to different clay raw materials, making it difficult to achieve excellent and stable dispersion effects.
Using a water-based polymer dispersant containing carboxylate and/or sulfonate, polymer dispersant is prepared by condensation of acrylic monomers with 2-acrylamide-2-methylpropanesulfonic acid monomers, and with small molecule dispersant For example, the complex of methylene bisnaphthalene sulfonate can regulate the mass ratio and pH value, form an electrostatic repulsion and hydration membrane stance hinder layer, and enhance the dispersion and stability of ceramic particles.
It realizes efficient dispersion of ceramic raw materials, reduces side effects, such as moisture content, broadens the scope of application of polymer dispersants, improves dispersion effect and stability, and reduces energy consumption.
Smart Images

Figure BDA0005045498180000021 
Figure BDA0005045498180000061 
Figure FDA0005045498160000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of dispersant preparation, and particularly relates to a water-based composite ceramic dispersant containing a high molecular polymer and a preparation method thereof. Background Art
[0002] When the ceramic raw materials are ball-milled to a certain time and fineness, they are often difficult to grind and even produce agglomeration and "reverse grinding" phenomena. At this time, dispersants are often added. Ceramic dispersants can be firmly adsorbed on the cracks of particles and can penetrate deep into the cracks, effectively breaking up the agglomeration in the powder, and obtaining a slurry with small particles, uniform distribution and near spherical shape, thereby playing a role in aiding grinding; at the same time, dispersants can reduce the interfacial tension between solid and liquid, effectively wet the particles, reduce the thickness of the hydration film, and obtain a slurry with good fluidity, achieving the effect of dilution and water reduction, reducing the water content of the green embryo, and reducing energy consumption in the ceramic manufacturing process.
[0003] Common ceramic dispersants in the prior art include inorganic salt dispersants, organic small molecule dispersants and polymer dispersants. Among them, polymer dispersants have become one of the development trends of ceramic dispersants due to their advantages such as good surface coverage and encapsulation effects and more stable dispersion systems.
[0004] However, the dispersants currently on the market often have shortcomings such as narrow dissolution range, side effects (such as high water content), poor versatility, and cannot be applied to different clay raw materials. Therefore, it is urgent to invent a polymer dispersant with good dispersing effect, stable dispersion, no side effects, and a wider range of application, so as to make up for the shortcomings of the existing technology and enrich the existing field of polymer ceramic dispersants. Summary of the invention
[0005] In view of the defects of the prior art, the purpose of the present invention is to provide an aqueous composite ceramic dispersant containing a high molecular weight polymer and a preparation method thereof, which can effectively play the role of the ceramic dispersant and achieve an excellent and stable dispersion effect; at the same time, the compounded composite ceramic dispersant has almost no side effects, and broadens the scope of application of the polymer dispersant, making up for the shortcomings of the prior art and enriching the existing field of polymer ceramic dispersants.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] On one hand, the present invention provides a water-based composite ceramic dispersant containing a high molecular weight polymer, wherein the dispersant comprises the following raw materials in parts by weight: 80 to 90 parts of a high molecular weight dispersant, 10 to 30 parts of a small molecular weight dispersant, 1 to 5 parts of hydrochloric acid, and 5 to 15 parts of deionized water;
[0008] The polymer dispersant is an aqueous polymer dispersant containing carboxylate and / or sulfonate.
[0009] Preferably, the preparation steps of the polymer dispersant are as follows:
[0010] Add acrylic acid monomer and deionized water of equal weight into the reactor, mix, pass nitrogen to deoxygenate, then add sulfonic acid monomer, raise the temperature to 55-65°C; slowly and continuously add initiator, react for 0.5-1.5h, keep warm for 1-2h, then adjust pH to alkaline, cool to room temperature to obtain polymer dispersant;
[0011] Further preferably, the preparation steps of the polymer dispersant are as follows:
[0012] Add acrylic acid monomer and deionized water into the reactor, mix, pass nitrogen to deoxygenate, then add sulfonic acid monomer, raise the temperature to 60°C; slowly and continuously add initiator, react for 1 hour, keep warm and react for 1.5 hours, then add ammonia water to adjust the pH to alkaline, cool to room temperature to obtain the polymer dispersant.
[0013] Preferably, the sulfonic acid monomer is 2-acrylamide-2-methylpropanesulfonic acid.
[0014] Preferably, the molar ratio of the acrylic acid monomer to the sulfonic acid monomer is (0.5-1):1.
[0015] Preferably, the structure of the polymer dispersant is as shown in Formula I:
[0016]
[0017] In the formula: x and n are integers of 0 to 100, and x and n are not 0 at the same time.
[0018] Preferably, the molecular weight of the polymer dispersant is 5000-10000 Da.
[0019] The invention utilizes the active reaction sites of acrylic acid monomers, introduces 2-acrylamide-2-methylpropane sulfonic acid monomers, and prepares a high molecular weight dispersant through unsaturated double bond condensation. The high molecular weight dispersant repels surrounding particles through multiple charges of the high molecular weight dispersant itself, thereby increasing the Zeta potential of the system, making it difficult for ceramic raw materials to flocculate, and achieving a dispersion effect superior to other high molecular weight dispersants in the prior art. Meanwhile, the high molecular weight dispersant has a molecular weight of 5000 to 10000 Da, so that a thicker adsorption layer is formed on the surface of ceramic particles by the high molecular weight dispersant, and the short-chain methyl group in the 2-acrylamide-2-methylpropane sulfonic acid monomer increases the density of the high molecular weight polymer network structure, and is adsorbed on the surface of ceramic particles in a ring or tail form, which significantly increases the steric hindrance effect, effectively prevents the peeling of the adsorption layer by external force, and increases the stability of the dispersant.
[0020] Preferably, the initiator is ammonium persulfate and ammonium bisulfite;
[0021] Further preferably, the added amount of the initiator is 0.1-0.5% of the total mass of the acrylic acid monomer and the sulfonic acid monomer.
[0022] Preferably, the small molecule dispersant is at least one of sodium gluconate, sodium methylene bis naphthalene sulfonate and sodium methylene bis methyl naphthalene sulfonate;
[0023] Further preferably, the small molecule dispersant is sodium methylene bisnaphthalene sulfonate.
[0024] Sodium methylenebisnaphthalene sulfonate is a common organic small molecule dispersant in the prior art, and its stability is difficult to ensure when used in ceramic dispersion. The applicant uses the prepared polymer dispersant and sodium methylenebisnaphthalene sulfonate in combination. There is no reactive active site between the small molecule dispersant and the polymer dispersant, and the same polar groups make the two have good compatibility, which has no adverse effect on the basic performance of the polymer dispersant.
[0025] Preferably, the mass ratio of the polymer dispersant to the small molecule dispersant is (5-7):1;
[0026] Further preferably, the mass ratio of the polymer dispersant to the small molecule dispersant is 6:1.
[0027] The applicant adjusted the mass ratio of the polymer dispersant and the small molecule dispersant to make the composite dispersant have a wider deflocculation range and a higher stable dispersion effect when used in ceramic dispersion at the preferred ratio. The possible reason is that when used in combination, the anionic dispersant sodium methylene bis naphthalene sulfonate assists in neutralizing the positive charge of the ceramic raw material, and the Na + The composite dispersion system has a strong hydration ability, and the diffuse double electric layer formed enhances the -SO3 in the polymer dispersant structure. - The electrostatic steric hindrance of -NH2 makes the ceramic raw material particles fully dispersed, the peripheral adsorption hydration film thickens, and the excess free water is released to reduce the viscosity of the system; at the same time, sodium methylene bisnaphthalene sulfonate fills the gaps that cannot be occupied by large molecules, increases the suspension force between particles, and enhances the fluidity and stability of the ceramic raw materials, ultimately achieving a better dispersion effect at a lower dosage.
[0028] On the other hand, the present invention provides a method for preparing a water-based composite ceramic dispersant containing a high molecular weight polymer, comprising the following steps: adding a small molecule dispersant to a high molecular weight dispersant, supplementing with deionized water, and adjusting the pH to a strong acid to obtain a composite ceramic dispersant.
[0029] Preferably, the method for preparing the aqueous composite ceramic dispersant containing a high molecular weight polymer comprises the following steps: adding a small molecule dispersant to a high molecular weight dispersant, supplementing with deionized water, and adjusting the pH to 0.5 to 0.6 to obtain a composite ceramic dispersant.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The aqueous composite ceramic dispersant containing a high molecular weight polymer provided by the present invention can efficiently disperse inorganic particles in ceramic slurry at a low dosage through electrostatic repulsion and the steric hindrance layer formed by long polymer chains, and has a wider range of applications.
[0032] (2) The aqueous composite ceramic dispersant containing a high molecular weight polymer provided by the present invention is prepared by condensing a preferred acrylic acid monomer and a 2-acrylamide-2-methylpropanesulfonic acid monomer to prepare a high molecular weight polymer with a high Zeta potential and a dense network structure, preferably with a molecular weight of 5000 to 10000 Da. The polymer is adsorbed on the surface of ceramic particles in a ring or tail form, effectively preventing the peeling of the adsorption layer by external forces, increasing the steric hindrance effect, and achieving stable dispersion.
[0033] (3) The aqueous composite ceramic dispersant containing a high molecular weight polymer provided by the present invention is obtained by compounding a high molecular weight dispersant and a small molecular weight dispersant. The two have good compatibility and synergistically enhance the deflocculation range of the system, so that the ceramic raw material particles are fully dispersed, the peripheral adsorption hydration film is thickened, and the excess free water is released, thereby reducing the side effect of the water content and achieving a better dispersion effect at a lower dosage. DETAILED DESCRIPTION
[0034] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0035] Unless otherwise specified, the reagents used below can be easily obtained from commercial companies.
[0036] In particular, in the following examples, the sulfonic acid monomer is 2-acrylamide-2-methylpropanesulfonic acid monomer, the initiator is ammonium persulfate and ammonium bisulfite, and the small molecule dispersant is sodium methylene bisnaphthalene sulfonate.
[0037] Preparation Example 1
[0038] Add 7 mol acrylic acid and an equal weight of deionized water into the reactor, mix, pass nitrogen to deoxygenate, then add 8.8 mol sulfonic acid monomer, raise the temperature to 60°C; slowly and continuously add 5.8 mL initiator, react for 1 hour, keep warm for 1.5 hours, then add 11 mol ammonia water to adjust the pH to alkaline, cool to room temperature to obtain polymer dispersant A.
[0039] Preparation Example 2
[0040] Add 5 mol acrylic acid and an equal weight of deionized water into the reactor, mix, pass nitrogen to deoxygenate, then add 12.5 mol sulfonic acid monomer, raise the temperature to 60°C; slowly and continuously add 7.4 mL initiator, react for 1 hour, keep warm for 1.5 hours, then add 12 mol ammonia water to adjust the pH to alkaline, cool to room temperature to obtain polymer dispersant B.
[0041] Example 1
[0042] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 85 parts of a high molecular weight dispersant A, 14 parts of a small molecular weight dispersant, 2.5 parts of hydrochloric acid and 10 parts of deionized water.
[0043] The method for preparing the aqueous composite ceramic dispersant containing a high molecular weight polymer in this embodiment comprises the following steps: adding a small molecule dispersant to a high molecular weight dispersant A, supplementing with deionized water, and adjusting the pH to 0.5 to obtain the composite ceramic dispersant.
[0044] Example 2
[0045] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 80 parts of a high molecular weight dispersant A, 16 parts of a small molecular weight dispersant, 1 part of hydrochloric acid and 15 parts of deionized water.
[0046] The preparation method of the aqueous composite ceramic dispersant containing high molecular weight polymer in this embodiment is the same as that in Example 1.
[0047] Example 3
[0048] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 90 parts of a high molecular weight dispersant A, 13 parts of a small molecular weight dispersant, 5 parts of hydrochloric acid and 5 parts of deionized water.
[0049] The preparation method of the aqueous composite ceramic dispersant containing high molecular weight polymer in this embodiment is the same as that in Example 1.
[0050] Example 4
[0051] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 80 parts of a high molecular weight dispersant A, 30 parts of a small molecular weight dispersant, 2.5 parts of hydrochloric acid and 10 parts of deionized water.
[0052] The preparation method of the aqueous composite ceramic dispersant containing high molecular weight polymer in this embodiment is the same as that in Example 1.
[0053] Example 5
[0054] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 95 parts of a high molecular weight dispersant A, 10 parts of a small molecular weight dispersant, 2.5 parts of hydrochloric acid and 10 parts of deionized water.
[0055] The preparation method of the aqueous composite ceramic dispersant containing high molecular weight polymer in this embodiment is the same as that in Example 1.
[0056] Example 6
[0057] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 85 parts of a high molecular weight dispersant B, 14 parts of a small molecular weight dispersant, 2.5 parts of hydrochloric acid and 10 parts of deionized water.
[0058] The preparation method of the aqueous composite ceramic dispersant containing a high molecular weight polymer in this embodiment is the same as that in embodiment 1, wherein the high molecular weight dispersant B replaces the high molecular weight dispersant A.
[0059] Example 7
[0060] A water-based composite ceramic dispersant containing a high molecular weight polymer comprises the following raw materials in parts by weight: 85 parts of a high molecular weight dispersant A, 14 parts of a small molecular weight dispersant, 2.5 parts of hydrochloric acid and 10 parts of deionized water.
[0061] The preparation method of the aqueous composite ceramic dispersant containing high molecular weight polymer in this embodiment is the same as that in embodiment 1, wherein sodium polyacrylate is used to replace sodium methylene bisnaphthalene sulfonate.
[0062] Performance Test:
[0063] The composite ceramic dispersant is added into the ceramic raw material in an amount of 0.3wt%.
[0064] 1. Mud fluidity: The ceramic raw material added with the composite ceramic dispersant is ball-milled in a fast ball mill for 5 minutes. The ceramic slurry is left to stand for 0 hours and 0.5 hours respectively. The flow time required for the slurry to flow through the filled Tu-4 cup is used to represent the mud fluidity.
[0065] 2. Thickening degree: Thickening degree = τ0.5h / τ0h×100%, which is used to characterize the stability of the slurry. τ0.5h is the time taken for the slurry to flow out of the Tu-4 cup after standing for 0.5h, and τ0h is the time taken for the slurry to flow out of the Tu-4 cup after standing for 0h.
[0066] The specific test results of the dispersants of Examples 1-7 obtained according to the above test method are shown in Table 1.
[0067] Table 1
[0068]
[0069] As can be seen from Table 1 above, the composite ceramic dispersant provided by Examples 1-5 of the present invention can effectively improve the dispersibility of ceramic slurry. Observing the data of Examples 1-3 and Examples 4-5, it can be seen that under the preferred compounding ratio of polymer and small molecule dispersants, the initial and 0.5h mud fluidity is good, and the thickness is small, and the dispersing effect of the composite ceramic dispersant is sufficient. From Example 1-3 and Example 6, it can be seen that the mud fluidity decreases. This is because when the polymerization ratio of long carbon chain monomers in the polymer increases, the network entanglement effect is too strong, and the viscosity of the system increases. This shows that the polymer dispersant prepared by the preferred polymerization ratio of the two monomers of the present invention has excellent dispersibility; in addition, Example 7 replaces the preferred small molecule dispersant with other dispersants in the prior art such as sodium polyacrylate, and it is found that its compounding effect with the polymer dispersant decreases, and the thickness increases. It shows that the composite ceramic dispersant of the preferred sodium methylene bis naphthalene sulfonate compounded with a polymer dispersant has significant advantages.
[0070] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A water-based composite ceramic dispersant containing a high molecular weight polymer, characterized in that: The dispersant comprises the following raw materials in parts by weight: 80-90 parts of a polymer dispersant, 10-30 parts of a small molecule dispersant, 1-5 parts of hydrochloric acid and 5-15 parts of deionized water; The polymer dispersant is an aqueous polymer dispersant containing carboxylate and / or sulfonate.
2. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 1, characterized in that: The preparation steps of the polymer dispersant are as follows: Add acrylic acid monomer and deionized water of equal weight into the reactor, mix, pass nitrogen to deoxygenate, then add sulfonic acid monomer, raise the temperature to 55-65°C; slowly and continuously add initiator, react for 0.5-1.5h, keep warm for 1-2h, then adjust pH to alkaline, cool to room temperature to obtain polymer dispersant.
3. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 2, characterized in that: The sulfonic acid monomer is 2-acrylamide-2-methylpropanesulfonic acid.
4. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 2, characterized in that: The molar ratio of the acrylic acid monomer to the sulfonic acid monomer is (0.5-1):
1.
5. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 1, characterized in that: The structure of the polymer dispersant is as shown in Formula I: In the formula: x and n are integers of 0 to 100, and x and n are not 0 at the same time.
6. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 5, characterized in that: The molecular weight of the polymer dispersant is 5000-10000Da.
7. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 2, characterized in that: The initiators are ammonium persulfate and ammonium bisulfite.
8. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 1, characterized in that: The small molecule dispersant is at least one of sodium gluconate, sodium methylene bis-naphthalene sulfonate and sodium methylene bis-methylnaphthalene sulfonate.
9. The aqueous composite ceramic dispersant containing a high molecular weight polymer according to claim 1, characterized in that: The mass ratio of the polymer dispersant to the small molecule dispersant is (5-7):
1.
10. A method for preparing the aqueous composite ceramic dispersant containing a high molecular weight polymer according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding a small molecule dispersant into a high molecule dispersant, supplementing with deionized water, and adjusting the pH to a strong acid to obtain a composite ceramic dispersant.
